Making technology invisible in the developing world - Marsden, Gary; Cutrell, Ed; Jones, Matt; Nanavati, Amit A.; Rajput, Nitendra (Computer, 2012)
Those of us in the developed world live in an environment where information is literally everywhere. In addition to physical media such as newspapers, books, and magazines, invisible signals carry data to our smartphones, tablets, and laptops. The uncountable pages in the World Wide Web leave nearly no question unanswered, and using mobile devices to obtain data has become natural. Information and communication technology (ICT) has become so convenient that we scarcely think about it. For those in the developing world, however, information is less than pervasive. Although many people have a cell phone, access costs and user literacy barriers make acquiring data a deliberate, complicated, and expensive undertaking. Those in the developing world can’t effortlessly pluck invisible information from the air and must go to great lengths to find what they need. Three representative ICT projects—two based in India, and the other in South Africa—seek to make access to information ubiquitous in the developing world. These systems fit naturally into the users’ environment, effectively making the technology invisible and providing the underprivileged with natural, convenient access to a wide range of data sources.